Primary Hyperparathyroidism in Pregnancy: A Two-Case Report and Literature Review - A. D. Herrera-Martínez; R. Bahamondes-Opazo; R. Palomares-Ortega; C. Muñoz-Jiménez; M. A. Gálvez-Moreno; J. M. Quesada Gómez (Case Reports in Obstetrics and Gynecology)
Primary hyperparathyroidism (PHPT) in pregnant women is an uncommon disease. It could be easily misdiagnosed because of physiologic changes during pregnancy; in some cases, patients could remain asymptomatic maintaining elevated calcium serum levels, and this situation represents a threat to the health of both mother and fetus. We present two cases of PHPT during pregnancy and their evolution after surgical treatment in the second trimester; there were no observed complications during pregnancy or delivery in our patients. Early diagnosis and medical/surgical treatment in PHPT are necessary for avoiding maternal and fetal complications which could not be predicted based on duration or severity of hypercalcemia. An appropriate management of PHPT during pregnancy is necessary for preserving the health of both the woman and the fetus.